ANALISIS PENGARUH KEUANGAN DIGITAL TERHADAP KINERJA UMKM PADA KOTA PONTIANAK DAN SINGKAWANG - Sri Rejeki, Yosepin; Kristiawati, Endang; Febriati, Febriati; Mayasafitri, Rina (Jurnal Akuntansi, Auditing dan Investasi, 2024)
The use of digital finance can be utilized by MSME players to improve the quality of their business. With the trendof using digital finance which has become a lifestyle of society, does it affect the improvement of MSMEperformance. The purpose of this study was to determine and analyze the effect of digital finance on theperformance of MSMEs in Pontianak and Singkawang cities. This research method uses a quantitative approachwith the research population being MSMEs in West Kalimantan with purposive sampling. This techniquesucceeded in getting 162 MSME players in Pontianak and Singkawang cities. The data was collected bydistributing questionnaires via google form and print. The data analysis technique in this study used validity tests,reliability tests, classical assumption tests and hypothesis testing. Data management in this study used SPSSsoftware. Based on the results of this study, it can be concluded that digital finance has a significant effect on theperformance of MSMEs in Pontianak and Singkawang cities.